Continuous time system identification: a selected critical survey. Part II. Input error methods and optimal projection equations. - Khải, Ngô Minh; Minh, Hoàng; Tuyên, Trương Nhữ; San, Nguyễn Ngọc (Journal of Computer Science and Cybernetics, 2013)
-